Peningkatan Hasil Belajar Batik Jumputan Melalui Model Project Based Learning Pada Siswa SMP - Wulandari, Wulandari (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The learning outcomes of Batik Jumputan Decorative Varieties at SMP Negeri 3 Grogol still have many problems faced by students, namely the lack of interest in learning and creativity possessed by students. In addition, from the learning environment factors at school, the media for learning arts and culture at SMP 3 Grogol is also limited. This study aims to improve the learning outcomes of Arts and Culture on decorative motifs on tie-dye batik materials through the Project Based Learning model for junior high school students. The subjects in this study were taken randomly with a total of 32 students, data collection was carried out through observation, documentation and tests. Data analysis was carried out using comparative descriptive techniques. Data collection Data analysis was carried out in 3 (three) stages including: data reduction, data presentation and drawing conclusions or verification. Empirical data from the results of the study showed that in cycle I, learning outcomes showed the lowest value of 68, the highest value of 85, and an average value of 71.88, while students who had not completed were 9 or 28.12% of the total 32 students. In cycle I, the Project Based Learning Model Design was used. In cycle II learning, the learning outcomes showed the lowest score of 74, the highest score of 90, and the average score of 80.25. Based on the results of the study, it can be concluded that through the application of the Project Based Learning Model, it can improve the learning outcomes of Arts and Culture on decorative motifs on tie-dye batik materials for junior high school students. This is indicated by the increase in learning outcomes in each cycle.